THE PECULIARITIES OF THE ORGANIZING OF THE CATERING FOR THE STUDENTS OF THE CITY SCHOOLS - Bezpala, Z.V.; Sargosh, O.D. (World of Medicine and Biology, 2013)
The paper analyzes and given the hygienic assessment of nutritional status of children in secondary schools of Poltava in the period from 2007 to 2012. Studied the actual nutrition of organized groups of children in 40 secondary schools of Poltava. The analysis of the school catering for the city schoolchildren of the secondary schools in Poltava revealed the following facts: 1.The consumption of hot meals by pupils of the 1st-11thforms since 2007 to 2012 was the highest. It reached 89%.The consumption of hot meals and pantry products by these students was 98% by the end of 2012. 2.The consumption of hot meals by pupils of the 1st -11th forms is much better than of the students of the 5th -11th forms. 3. The system of the nutrition children at school needs to be regulated and the further research should be conducted.